Equity Valuation Effects of Foreign Capital Expenditures: The Role of Property Rights (International Journal of Banking and Finance, 2003)
We examine common stock price reactions to offshore capital expenditures undertaken by U.S. multinational firms. Arguments based on optionality and expropriability lead to predicted price reactions conditioned on the degree of ambiguity in property rights enforcement in the host country. Our findings based on 159 foreign investment decisions reveal a significant influence of property rights ambiguity on the valuation effect. For investment in countries where property rights are enforced as reliably as in the U.S., firms experience an average increase in equity value of $41.83 million, or $1.614 per dollar invested. For countries with greater ambiguity in enforcement, firms experience an average loss of $39.28 million. Controlling for risk, leverage and differential taxes, we find that property rights ambiguity is the dominant explanatory factor for the market’s reaction to these decisions.